PREMARITAL TRAINING AND COUNSELING (Studi Deskriptif Bimbingan Pranikah Di KUA Pragaan Dalam Membentuk Keluarga SAMARA) - Heri Fadli Wahyudi; Maulidah Maulidah; Izzat Amini; Ghozi Mubarok (Bayan lin-Naas : Jurnal Dakwah Islam, 2023)
ABSTRACT:Â Being a sakinah, mawadah, warahmah family, is the desire or even the ideal of all marriages, therefore to realize this, the government provides a solution by holding a premarital course so that this desire is achieved, the method used in this study is a qualitative descriptive method that focuses on the role of premarital guidance at the Office of Religious Affairs (KUA) of Pragaan district, Sumenep in building a sakinah family,Â  Mawaddah, Warahmah. There are three objectives in this study, first to find out the strategy of this premarital course for prospective married couples in KUA Pragaan, second to find out how far the role of premarital courses in Pragaan sub-district so that they can maintain family integrity, and the third is how KUA's efforts in providing premarital courses to prospective brides in Pragaan. The results of this study revealed that the premarital course carried out by KUA Pragaan was carried out in accordance with the contents of the guidebook compiled by the Ministry of Religious Affairs, this catin course was carried out independently by KUA. To facilitate the application of carrying out the role of husband and wife for catins, the resource person delivered this premarital guidance using easy-to-understand and pleasant language, so that catin could form a family that sakinah mawaddah wa rahmah. But there are two obstacles that cause this catin course to be less effective, namely, first internal factors (facilities and finances) that exist in the KUA and the second is, external factors are members of the bride and groom who are not present and view that this premarital course is not so important.